Improving information literacy in higher education in an unorthodox way: the literature Potential for Acrl framework application - Sanches, Tatiana (2021)
The implementation of the ACRL Framework has been a challenge for higher education librarians. This study proposes an unconventional way of adopting the opportunities of literary reading to teach the six conceptual frames recommended by this guiding document. From a literature review on the importance that literary reading has in the individual's life as well as the experiences of higher education libraries in the promotion of literary reading, a reflection emerges on the opportunity to teach information skills in this context. The main objective of this work is to make a creative and innovative contribution to the practical and situated application of the ACRL Framework in a non-traditional context, exploring literary reading to explain concepts, dispositions, and practices. For each conceptual frame are listed examples and situated learning strategies, which can contribute to the acquisition of essential and structuring instruments of the mechanisms necessary for information skills. Regarding specifically reading comprehension, it is important to work on the ability to extract relevant information from written texts so that it becomes a powerful tool for obtaining and processing information, transversal learning, and social insertion and is not reduced to school learning, but reveals its potential in extra-scholarly contexts, such as reading groups, meetings with authors, or the constitution of specific collections for leisure reading in university libraries.